Analysis of the competitiveness of the tourism sector in the Maghreb Countries, Algeria, Tunisia, Morocco, during the period (2015-2019) - Khamsa, Saihi; Souad, Boulassas Madjda (The International tax journal, 2026)
This study aims to determine the importance of enhancing the competitiveness of the tourism sector in the Maghreb countries by analysing the competitiveness of the tourism sector in three Maghreb countries. (Algeria, Morocco and Tunisia), through a review of the components and indicators of tourism sector performance and then compare the indicators of tourism competitiveness of the three countries, as the study found that these countries have diverse and rich tourist destinations according to the World Tourism Organization in its annual reports 2015-2019 However, the weakness of tourism services and the fragility of infrastructure associated with tourism activity has been an obstacle to the achievement of the sector's objectives, and the study recently recommended the need to support the tourism sector.